When the online backs the street – the making of digitized political emotion: a case study of the Romanian anti-government protests. Issue 3 (3rd May 2020) - Stoicescu, Adrian
ABSTRACT: For the past few years, Romanian society has been involved with a strong opposition movement against the governing party which, using various pretexts, tries to pass legislative measures to help various high-ranking officials escape criminal charges. This opposition takes the form of actions both online and offline, and is characterized by bursts of emotional messages from both sides. This paper will analyse two such instances which differ in terms of their content, targets and strategies, communication channels, and patterns of viralization using two distinct types of emotional configurations: native emotions – those created and circulated within a particular group with shared emotions, and those created by a party and circulated within its opposing counterpart. The article will examine how the emotion is created, how it coagulates it target public, and how the emotional content viralizes and produces additional reactions employing a methodology relevant to media epidemiography.